2002
DOI: 10.1179/000349802125002293
|View full text |Cite
|
Sign up to set email alerts
|

Human cutaneous leishmaniasis caused by <I>Leishmania naiffi</I> is wide-spread in South America

Abstract: Four human cases of localized cutaneous leishmaniasis caused by Leishmania naiffi are reported. Two of the cases were infected in French Guiana, one in French Guiana or Martinique, and the other in Ecuador or Peru. The geographical distribution of L. naiffi is clearly larger than that initially reported. Three zymodemes were represented by the four isolates, confirming that there is intraspecific polymorphism in L. naiffi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 0 publications
2
36
0
5
Order By: Relevance
“…In the Amazon region only L. (V.) braziliensis was identified, but hybrid genotypes between L. (V.) panamensis/guyanensis and L. (V.) braziliensis had also been reported (Bañuls et al 1997). Furthermore, Pratlong et al (2002) identified L. naiffi in a German patient with CL suspected to be infected in this region.…”
Section: Parasite Distributionsmentioning
confidence: 95%
“…In the Amazon region only L. (V.) braziliensis was identified, but hybrid genotypes between L. (V.) panamensis/guyanensis and L. (V.) braziliensis had also been reported (Bañuls et al 1997). Furthermore, Pratlong et al (2002) identified L. naiffi in a German patient with CL suspected to be infected in this region.…”
Section: Parasite Distributionsmentioning
confidence: 95%
“…Surinam Darie et al, 1995;Pratlong et al, 2002;Fouque et al, 2007;van der Snoek et al, 2009;van Thiel et al, 2010;Felinto de Brito et al, 2012).…”
Section: Identification Of Leishmania Species From Patient Specimensunclassified
“…However, isolates from different polymorphic species show plesiomorphic similarities in their enzymatic or genetic profiles, suggesting that they may have originated from one primary sylvatic enzootic form. 80,81 Globally, although L. (V.) braziliensis [82][83][84][85][86][87][88][89][90] and in a lesser extent L. (V.) amazonensis 85,91 were shown to be highly polymorphic, L. (V.) naiffi, 45,82,83 L. (V.) guyanensis, 46,83,88 and L. (L.) deanei 92 were shown to have less diversity. Leishmania (V.) lainsoni was shown to be more invariant.…”
Section: Ecology Of Leishmania Species In the Gecmentioning
confidence: 99%
“…An intra-specific polymorphism has been reported in L. (V.) naiffi. 45 As suggested by Lainson and others, 173 if one considers that L. (V.) naiffi rarely produces a discernable skin lesion in hamsters, some infections may have been missed when a lesion was the sole detection method. Nonetheless, considering its clinical features and its incidence in the GEC, this parasite does not appear to be an important pathogen of humans.…”
Section: Diversity Strains Of L (V) Braziliensis Isolated Inmentioning
confidence: 99%
See 1 more Smart Citation